Role of pulses to modulate the nutritive, bioactive and technological functionality of cereal‐based extruded snacks: a review. (12th June 2021) - Sharma, Rajan; Sharma, Savita; Makroo, Hilal A.; Dar, B.N.
Summary: Pulses hold excellent nutritive potential owing to high‐quality protein content, dietary fibre, minerals, vitamins, oligosaccharides, polyphenols, tannins, phytosterols and several other bioactive constituents. These bio‐functional compounds impart significant health benefits by reducing the risk of several chronic complications such as hypertension, cancers, cardiovascular diseases and neurological concerns mainly through anti‐oxidative and radical scavenging mechanisms. These high protein ingredients when added to cereal‐based extruded snacks not only enhance the nutritive and bioactive profile of the resultant snacks but also modulate the techno‐functional attributes of the extrudates. Protein interactions with cereal‐based starch and other constituents result in structural variation at the macromolecular level consequently varying the physical, mechanical and techno‐functional properties including expansion ratio, bulk density, hydration properties, pasting characteristics and texture. The present review aimed at elaborating the nutritive and bio‐functional potential of pulses enriched cereal‐based expanded snacks. Further, significant emphasis has been given to the impact of pulse flour incorporation on functional, structural and mechanical properties of the cereal‐based extrudates. Abstract : Enhancement of functional and biological properties of cereal extrudates with incorporation of pulses.